Ethnopedogogyin Mathematics Education: B y UKI Toraja For The International - Lalan Langi, Evy; Palengka, Inelsi; Pakadang, Oktavianus Yandri (Yayasan Literasi Kita Indonesia, 2024)
This study investigates the application of ethnopedagogy in mathematics education at Universitas Kristen Indonesia (UKI) Toraja, focusing on its impact on international students. Ethnopedagogy, which integrates cultural contexts and values into teaching practices, aims to create a more inclusive and relevant learning environment. This research explores how UKI Toraja incorporates ethnopedagogical principles into its mathematics curriculum to support international students from diverse cultural backgrounds.The research examines various strategies employed by UKI Toraja, such as contextualizing mathematical problems with local cultural references, adapting teaching materials to reflect the diverse cultural experiences of international students, and utilizing collaborative learning approaches that respect and incorporate students' cultural perspectives. Through a combination of qualitative and quantitative methods, including surveys, interviews, and classroom observations, the study assesses the effectiveness of these ethnopedagogical strategies in enhancing student engagement, understanding, and academic performance.Ethnopedagogical approaches significantly improve international students' mathematical learning experiences by making content more relatable and engaging. The study also highlights the challenges faced in implementing these strategies, such as the need for continuous professional development for educators and the importance of developing culturally responsive resources.